The Kane Chronicles: The Red Pyramid - Book 1 - Riordan, Rick; Free, Kevin R.; Kellgren, Katherine (Grand Haven, MI Brilliance Audio, 2010)
Egyptologist Dr. Julius Kane accidentally unleashes the Egyptian god Set, who banishes the doctor to oblivion and forces his two children to embark on a dangerous journey to save him.
Unabridged.
Compact discs.
Read by Kevin R. Free and Katherine Kellgren.
Keywords: Children's audiobooks; Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Mythology, Egyptian -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Secrets -- Fiction; Audiobooks